Ushul Nahwi During Covid-19: How to Teach the Students of University? l Ushul al-Nahwi Khilala ‘Ashri Covid-19: Kaifa Tu’allimu Talabah al-Jami’ah? - Akmalia, Frida; Abdurrahman, Maman; Sopian, Asep (Universitas Islam Negeri Raden Intan Lampung, 2021)
In Arabic learning, the majority of university in Indonesia would ignore the study of Ushul Nahwi and emphasize on Arabic language skills development. This study presented the results and analysis about the implementation of Ushul Nahwi learning during Covid-19 outbreak in Arabic Education Study Program at one of the well-known universities in Indonesia. The research data was obtained from observation, interview and documentation. Observations was made directly and interview was conducted by interviewing 20 student teachers majoring Arabic education and 2 Ushul Nahwi lecturers in one of the universities in Bandung. In addition, documentation was done by collecting Ushul Nahwi learning plans and some photos during Ushul Nahwi learning. The results have shown that: 1) The components of Ushul Nahwi lesson plan for university consist of learning objectives, description for studying the origins of grammar, description of the subject, references or bibliography, and evaluation. 2) Implementation of Ushul Nahwi for Arabic Education Study Program is by using Zoom Meetings, Google Classroom, and Whatsapp. In Ushul Nahwi learning, five learning steps are applied at the 2nd to 12th meetings. 3) The strengths and weaknesses of Ushul Nahwi implementation in Covid-19 outbreak. The learning system has the advantage of facilitating students in the learning process. Thus, the weakness was caused by various problem during the process of learning and after the activity. These results are hopefuly useful as an illustration of the virtual Ushul Nahwi learning process and become a reference for the next researchers.